2009
DOI: 10.1002/lapl.200910043
|View full text |Cite
|
Sign up to set email alerts
|

Passively Q-switched mode-locking in a diode-pumped c-cut Nd:LuVO4laser with Cr4+:YAG

Abstract: A passively Q-switched and mode-locked c-cut Nd:LuVO4 laser at 1.06 μm using Cr 4+ :YAG absorber has been successfully demonstrated. A nearly 100% modulation depth of mode-locking was achieved. At pump power of 12.04 W, the maximum average output power of 0.64 W and Q-switched pulse envelop repetition rate of 60 kHz were obtained with absorber's initial transmission of 96%, while the highest Q-switched pulse energy of 14.11 μJ was achieved with initial transmission of 60%. The duration of mode-locked pulse wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…:YAG) has been widely used as passively Q switched saturable absorber [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Besides, Tet ravalent chromium ion has been recognized as a pop ular and efficient ion for obtaining tunable laser oper ating in the near infrared region (1.2-1.6 µm) [16][17][18][19].…”
Section: +mentioning
confidence: 99%
“…:YAG) has been widely used as passively Q switched saturable absorber [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Besides, Tet ravalent chromium ion has been recognized as a pop ular and efficient ion for obtaining tunable laser oper ating in the near infrared region (1.2-1.6 µm) [16][17][18][19].…”
Section: +mentioning
confidence: 99%
“…Recently, a new triple mixed vanadate crystal Nd:Lu 0.33 Y 0.37 Gd 0.3 VO 4 has been successfully fabri cated. The central wavelength of the fluorescence band at 1064.1 μm has a half maximum (FWHM) of 6.2 nm, which is even broader than those of the dou ble mixed crystals [19][20][21][22][23]. The diode pumped pas sively Q switched Nd:Lu 0.33 Y 0.37 Gd 0.3 VO 4 laser with a single walled carbon nanotube saturable absorber demonstrated that shorter pulse width and higher peak power can be generated.…”
Section: Introductionmentioning
confidence: 96%
“…The central wavelength of the flu orescence band at 1064.1 µm has a half maximum (FWHM) of 6.2 nm, which is even broader than Nd:Lu x Y 1 -x VO 4 . The related physical parameters are shown in table [25,26]. The diode pumped passively Q switched Nd:Lu 0.33 Y 0.37 Gd 0.3 VO 4 lasers with a sin gle walled carbon nanotube and Cr 4+ :YAG saturable absorber demonstrated that shorter pulse width and higher peak power can be generated [27,28].…”
Section: Introductionmentioning
confidence: 98%